Occult Pneumomediastinum - An Atypical Presentation of Chest Discomfort in a Patient with Depression - V, Haripriya Menon; R, Unnikrishnan (Journal of Pulmonology and Respiratory Research, 2024)
Pneumomediastinum (mediastinal emphysema) is an uncommon condition characterized by the accumulation of air or gas in the mediastinum. Here is a case of a 16-year-old female known to have depression who presented to the emergency department with complaints of shortness of breath, restlessness, chest discomfort, and hoarseness of voice for 2 days. She was initially diagnosed with panic attack, and later on clinical examination, surgical emphysema over the right supraclavicular area was noticed. Chest X-ray was found to be normal, and further imaging with high-resolution computed tomography (HRCT) of the thorax showed pneumomediastinum. In this report, the clinical presentations, radiological features, and management of pneumomediastinum will be discussed.